Perceptions of using e-learning applications in accounting at residential universities in South Africa: A social justice lens - Papageorgiou, E.; Van der Merwe, N.; Terblanche, W.; Lubbe, I. (South African Journal of Higher Education, 2024)
In a post-COVID world, higher education institutions are debating several divergent delivery modes, searching for the optimal approach, with many calling for change and embracing technology in the current space. However, institutions (and their students) may only be somewhat ready for e-learning, especially in developing economies such as South Africa, with its many social justice challenges. The COVID-19 period forced higher education into the e-learning space, and many students were left behind due to a lack of access, inequity, challenges related to diversity, and the inability to participate in learning. This study aimed to analyse students’ perceptions and experiences with using e-learning applications through the lens of social justice. Qualitative data were collected from accounting students registered at four South African residential universities (n = 1864). Themes emerged from the data analysis performed using a qualitative research analysis tool. These themes were classified and discussed under four social justice principles. The findings indicate a clear link between student experiences of e-learning and social justice, with some students finding successful participation in e-learning significantly more challenging than others. The nature of these challenges should be informative for institutions that are considering moving learning to online modes. Higher education curriculum developers, policymakers, institutions, and academics are encouraged to consider social justice principles when considering adapting to online or blended learning.